The capital-energy complementarity debate revisited - Solow, John L. (American Economic Review, 1987)
This paper argues that the empirical disagreement as to whether capital and energy are complements or substitutes is not likely to be reconciled with aggregate data. It demonstrates that price-induced changes in the composition of output can cause either outcome in the aggregate, even if no technical substitution is possible. Substitution by consumers and changes in the relative incomes of consumers and foreigners are identified as key factors in determining which outcome arises. Copyright 1987 by American Economic Association.